The Effects of Various Essential Oils as Antibacterial Agents on Fresh-Cut Apples cv. ‘Manalagi’ - Utama, Nafi Ananda (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2018)
The fast-paced lifestyle of modern consumers warrants the need for a quick and minimally processed food. For fresh products, this means healthy fresh food, convenient, and microbiologically safe food items produced with environmentally friendly methods. In this research, antimicrobial effects of carboxymethyl cellulose based-edible film containing different concentrations of essential oils (0.7 % cinnamon, 0.7 % lemongrass, 3 % lemon, and 0.1 % betel, w/v) as antibacterial agents on fresh-cut apples cv. Manalagi were studied. Measurements of weight loss, total titratable acidity (TTA), reducing sugar, microbial growth and sensory quality were determined at 0, 3, 6, 9, 12 and 15 days of storage (4 ± 1 °C, 75 ± 10 % RH). The results of the research showed that the application of 0.7% lemongrass oil on 1 % CMC gave the best result in inhibiting the bacterial growth and prolong the storage life of fresh-cut apples cv. Manalagi. The incorporation of 0.7 % (w/v) lemongrass and lemon 3 % (w/v) in coating formulation maintained the sensory scores (aroma and appearance) of fresh-cut apples during nine days of storage.